Subjective Norms, Financial Conditions, and Online Tax Applications Influence on Taxpayer Compliance Moderated Providing Study Area Tax Incentives at Tangerang City Hotels and Restaurants - Anggraeni, Virdha; Apollo Daito (Dinasti International Journal of Economics, Finance & Accounting, 2022)
The Covid-19 pandemic requires the state to make policies to limit people’s activities, one of which is the implementation of temporary business closures at restaurants and reducing business operating hours. This greatly affects economic stability, so the government makes policies by providing incentives and tax relaxation as an effort to maintain the local economy as well as to maintain local taxpayer compliance. This study aims to determine the effect of subjective norms, financial conditions, and online tax applications on taxpayer compliance, besides that this study will also examine local tax incentives that can be used as moderating variables. This research was conducted in Tangerang City, Banten Province. The type of data used in this research is primary data with a questionnaire data collection method. The number of samples in this study was 303 with the calculation of the slovin formula. The data analysis method used is multiple linear regression analysis and interaction test, while the data processing of this study uses SPSS 26 software. The hypothesis testing in this study is that subjective norms, financial conditions, and online tax applications have a significant positive effect on compliance. The tax incentives are not able to moderate subjective norms, financial conditions, and online tax applications on taxpayer compliance.